A Formative Assessment Based on Revised Bloom’s Taxonomy in Merdeka Curriculum English Textbook (Universitas Negeri Semarang, 2021)
This study was focused on the textbook evaluation which focused on formative assessment in the form of exercises provided in the Bahasa Inggris: Working in Progress Textbook published by Ministry of Education and Culture for senior/vocational high school level in 2022. This study used descriptive evaluative study in which all exercises were analysed toward revised Bloom’s taxonomy as well as Merdeka Curriculum. The analysis also examined the Merdeka Curriculum toward revised Bloom’s taxonomy. The results of the study showed that the formative assessments in the form of exercises provided by the textbook have successfully facilitated the cognitive process and knowledge dimensions from revised Bloom’s taxonomy. It was reflected on the analysis that showed that the exercises were arranged hierarchically following from the simple instruction to the complex instructions in each chapter of the textbook. Moreover, the formative assessment as realized in the textbook exercises have already compatible with the Merdeka curriculum especially in fulfilling the learning objectives of Xth grade. As the textbook is designed for Xth throughout the semester, every chapter of the textbook has already consisted of assessments evaluating the student’s listening, speaking, reading, viewing, writing, and presenting skills holistically. Regarding the evaluation of the Merdeka Curriculum toward revised Bloom’s taxonomy, the finding confirmed that cognitive process and knowledge dimensions of Revised Bloom’s taxonomy were reflected in all language competences from the learning objectives stated in Merdeka curriculum for Xth grade of senior high school. It is advised for the exercise designer to employ an appropriate level of the updated Bloom's taxonomy to achieve the learning objectives in order to create an activity that may represent the curriculum's learning objectives.